The osteology of Periptychus carinidens: A robust, ungulate-like placental mammal (Mammalia: Periptychidae) from the Paleocene of North America. - Sarah L Shelley; Thomas E Williamson; Stephen L Brusatte (PLoS ONE)
Periptychus is the archetypal genus of Periptychidae, a clade of prolific Paleocene 'condylarth' mammals from North America that were among the first placental mammals to radiate after the end-Cretaceous extinction, remarkable for their distinctive dental anatomy. A comprehensive understanding of the anatomy of Periptychus has been hindered by a lack of cranial and postcranial material and only cursory description of existing material. We comprehensively describe the cranial, dental and postcranial anatomy of Periptychus carinidens based on new fossil material from the early Paleocene (Torrejonian) of New Mexico, USA. The cranial anatomy of Periptychus is broadly concurrent with the inferred plesiomorphic eutherian condition, albeit more robust in overall construction. The rostrum is moderately elongate with no constriction, the facial region is broad, and the braincase is small with a well-exposed mastoid on the posterolateral corner and tall sagittal and nuchal crests. The dentition of Periptychus is characterized by strongly crenulated enamel, enlarged upper and lower premolars with a tall centralised paracone/protoconid. The postcranial skeleton of Periptychus is that of a robust, medium-sized (~20 Kg) stout-limbed animal that was incipiently mediportal and adopted a plantigrade stance. The structure of the fore- and hindlimb of Periptychus corresponds to that of a typically terrestrial mammal, while morphological features of the forelimb such as the low tubercles of the humerus, long and prominent deltopectoral crest, pronounced medial epicondyle, and hemispherical capitulum indicate some scansorial and/or fossorial ability. Most striking is the strongly dorsoplantarly compressed astragalus of Periptychus, which in combination with the distal crus and calcaneal morphology indicates a moderately mobile cruropedal joint. The anatomy of Periptychus is unique and lacks any extant analogue; it combines a basic early placental body plan with numerous unique specializations in its dental, cranial and postcranial anatomy that exemplify the ability of mammals to adapt and evolve following catastrophic environmental upheaval.